Facet Articular Irregularity Is the Most Relevant Risk Factor for Rapidly Progressive Degenerative Cervical Myelopathy - Yasuhiro Takeshima; Ai Okamoto; Shohei Yokoyama; Fumihiko Nishimura; Ichiro Nakagawa; Young-Soo Park; Hiroyuki Nakase (Neurospine, 2023)
Objective Facet articular irregularity is associated with rapidly progressive degenerative cervical myelopathy (DCM). However, its significance compared with other known risk factors remains unknown. Therefore, this retrospective study aimed to clarify the potential impact of facet articular irregularity as a risk factor for rapid DCM progression. Methods This study included 141 consecutive patients with DCM who underwent surgical treatment at our institution. Clinical variables and radiological findings related to DCM progression were collected. Imaging findings were analyzed at the segmental level of myelopathy in each case. The patients were divided into 2 groups based on the presence or absence of rapid DCM progression, and independent risk factors were determined using logistic regression analyses. Results Overall, 131 patients with a mean age of 63.9±12.6 years were analyzed; 27 patients (20.6%) were classified into the rapid DCM progression group. The mean age was significantly higher in the rapid progression group than in the slow progression group (72.4±9.6 vs. 61.7±12.4, p<0.001). According to univariate analysis, facet articular irregularity, dynamic segmental translation (≥1.6 mm), upper cervical spine involvement above C4–5, history of cerebrovascular events, preceding minor trauma, local lordotic angle (≥4.5°), diabetes, hypertension, ligamentum flavum hypertrophy, and age were independent risk factors. Additionally, multivariate analysis showed that facet articular irregularity was the highest risk factor for rapid DCM progression (p=0.001). Conclusion Facet articular irregularity is the most clinically significant finding among the known risk factors in patients with rapid DCM progression.